The relationship between coronary artery severity and insulin resistance in patients with impaired glucose tolerance and metabolic syndrome - Yasser Gaber Metwally; Heba Kamal Sedrak; Inas Fahiem Shaltout (SpringerOpen, 2020)
Abstract Background The relation between metabolic syndrome (MS) and coronary artery disease (CAD) is multifactorial, and the well-known risk factors can explain only about 25% of the disease as the relation between insulin resistance (IR) on top of MS and severity of CAD still a subject of debate with conflicting data. Also, IR and glucose intolerance are included in the definition of metabolic syndrome only by some associations. So, the aim of this research was to analyze the the relation between CAD severity (measured by the modified Gensini score) and the different components of the metabolic syndrome including insulin resistance and glucose intolerance. Results Out of 70 patients enrolled, 71.4% represented impaired glucose tolerance group (IGT group; n = 50) and 28.6% represented normal glucose tolerance group (NGT group; n = 20). The following variables were significantly greater among the IGT group including BMI (30.19 ± 2.27 vs 23.62 ± 2.92; P < 0.001), waist circumference (105.09 ± 8.02 vs 92.89 ± 19.92; P < 0.001), frequency of hypertension (80% vs 50%; P = 0.012), 2 h post prandial glucose (164 ± 30 vs 110 ± 20; P < 0. 04), fasting insulin (9.2 ± 1.2 vs 5.1 ± 4.3; P = 0.003), HOMA-IR (3.03 ± 0.12% vs 1.9 ± 0.12, P < 0.001), serum uric acid (4.8 ± 1.3 vs 5.8 ± 2.6; P = 0.03), mean modified Gensini score (22.3 ± 9.2 vs 15.4 ± 6.8; P < 0.001), while the mean serum HDL was significantly higher among the NGT group (40.8 ± 10.1 vs 50.6 ± 10.2; P < 0.001). There was a positive correlation between HOMA-IR; hs-CRP; MS-related variables (including waist circumflex; BMI; serum uric acid; HDL; TG);and the modified Gensini score (for HOMA, r = 0.63; P < 0.001). Several predictors for high scores of modified Gensini were noted in multiple regression analysis; however, out of those several predictors, HOMA-IR was the strongest one (OR = 4.0, 95% CI = (2.04-7.08). Conclusion IR is an independent risk factor for CAD severity in patients with IGT and MS. In patients with IR; those with aggressive CAD (or with a positive family history of premature CAD), IGT should be managed aggressively even before any evidence of frank diabetes. IR workup should be recommended among the other standard workup for those patients, if documented, interventions targeted against IR should be considered among the other standard management.